Status of Water Quality Subject to Sand Mining in the Kelantan River, Kelantan - Tan Peck Yen; Rohasliney H (Tropical Life Sciences Research, 2013)
This paper aimed to describe the effects of sand mining on the Kelantan River with respect to physical and chemical parameter analyses. Three replicates of water samples were collected from five stations along the Kelantan River (November 2010 until February 2011). The physical parameters included water temperature, water conductivity, dissolved oxygen (DO), pH, total dissolved solids (TDS), total suspended solids (TSS) and turbidity, whereas the chemical parameters included the concentration of nitrogen nutrients such as ammonia, nitrate and nitrite. The Kelantan River case study revealed that TSS, turbidity and nitrate contents exceed the Malaysian Interim National Water Quality Standard (INWQS) range and are significantly different between Station 1 (KK) and Station 3 (TM). Station 1 has the largest variation of TDS, TSS, turbidity and nitrogen nutrients because of sand mining and upstream logging activities. The extremely high content of TSS and the turbidity have caused poor and stressful conditions for the aquatic life in the Kelantan River. Pensampelan kualiti air di sepanjang Sungai Kelantan telah dijalankan pada November 2010 hingga Feberuari 2011 di lima stesen yang dipilih. Pensampelan ini bertujuan untuk menggambarkan tentang keadaan status kualiti air di Sungai Kelantan. Analisis fizikal seperti konduktiviti, oksigen terlarut (DO), pH, jumlah pepejal terlarut (TDS), jumlah pepejal terampai (TSS) dan kekeruhan telah dijalankan. Kajian juga melibatkan analisis kimia nutrien nitrogen seperti ammonia, nitrat dan nitrit. Hasil kajian mendapati TSS, kekeruhan dan kandungan nitrat melebihi piawaian kualiti air kebangsaan (INWQS) dan terdapat perbezaan antara Stesen 1 (KK) dan Stesen 3 (TM). Variasi nilai kandungan TDS, kekeruhan dan nutrien nitrogen di Stesen 1 secara keseluruhan adalah besar kerana faktor perlombongan pasir di sepanjang sungai dan aktiviti pembalakan di kawasan hulu sungai. Kandungan TSS yang sangat tinggi dan kekeruhan telah mewujudkan keadaan yang tidak memuaskan dan memberi tekanan untuk hidupan akuatik di Sungai Kelantan.